2019
DOI: 10.1111/ans.15480
|View full text |Cite
|
Sign up to set email alerts
|

Novel systemic inflammation response index to predict prognosis after thoracoscopic lung cancer surgery: a propensity score‐matching study

Abstract: Background Our propensity score‐matching (PSM) study evaluated the prognostic significance of systemic inflammation response index (SIRI) for patients undergoing video‐assisted thoracoscopic surgery lobectomy for non‐small‐cell lung cancer (NSCLC). Methods This study was conducted on prospectively maintained database in our institution between December 2013 and March 2015. Pre‐operative SIRI was calculated by peripheral monocyte × neutrophil/lymphocyte counts. Survival analysis was performed to distinguish dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 17 publications
1
34
1
Order By: Relevance
“…And for NPC and AEG [ 17 , 22 ], the AUC value was higher for SIRI compared with the NLR, PLR, and MLR at both the 3- and 5-year follow-up. SIRI also achieved the largest AUCs compared with those of NLR, PLR, and lymphocyte-to-monocyte ratio (LMR) and was the only significant discriminator for OS and DFS in the propensity score matching cohort in NSCLC [ 21 ]. Besides, SIRI could more accurately predict OS of ESCC patients compared with the TNM staging system in the nomogram [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…And for NPC and AEG [ 17 , 22 ], the AUC value was higher for SIRI compared with the NLR, PLR, and MLR at both the 3- and 5-year follow-up. SIRI also achieved the largest AUCs compared with those of NLR, PLR, and lymphocyte-to-monocyte ratio (LMR) and was the only significant discriminator for OS and DFS in the propensity score matching cohort in NSCLC [ 21 ]. Besides, SIRI could more accurately predict OS of ESCC patients compared with the TNM staging system in the nomogram [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hu et al [31] found that high-sensitivity C-reactive protein in non-obese radiotherapy patients with malignant tumors could predict grade 4 skin toxicity, and advise doctors to change treatment options. Recently, the prognostic importance of SIRI for patients with renal, pancreatic and nasopharyngeal cancers has been con rmed [25,[32][33][34][35][36]. The higher the SIRI score is, the shorter the disease-free survival and OS.…”
Section: Discussionmentioning
confidence: 99%
“…To reduce the impact of confounding factors, we formulated a propensity score matching (PSM) model by the nearest neighbor method with a 0.2 caliper width and 1:1 ratio propensity score matching. In the PSM model, the components of the ULR could not participate in the matching [ 14] , which indicated that the serum markers from routine blood and biochemical tests were not taken into account in the PS balance.…”
Section: Methodsmentioning
confidence: 99%